Comparison of delayed versus immediate coloanal anastomosis in patients with low rectal cancer: a recent meta-analysis - Wang, Yonghong; Liu, Ke; Zhou, Wenjie; Dan, Jie; Zhu, Mingjie; Chen, Lei; He, Wanbin; Li, Ming; Li, Jiangpeng (Frontiers in Oncology, 2026)
BackgroundIn sphincter-preserving surgery for low rectal cancer (LRC), Immediate coloanal anastomosis (ICA) combined with prophylactic ileostomy remains the standard approach. However, this procedure is associated with the need for a second operation to reverse the stoma and risks of stoma-related complications. Delayed coloanal anastomosis (DCA) has recently regained attention as an alternative strategy, particularly in the context of evolving principles of minimally invasive surgery and enhanced recovery after surgery (ERAS). This meta-analysis aimed to systematically evaluate and compare DCA and ICA in terms of perioperative outcomes, postoperative complications, and oncological efficacy.MethodsFollowing the PRISMA guidelines, we conducted a comprehensive literature search across PubMed, MEDLINE, Embase, Cochrane Library, Web of Science, and the Chinese Biomedical Literature Database (CBM) from database inception to October 2025. We included clinical studies comparing DCA and ICA for the treatment of LRC. The Risk of Bias 2 (ROB2) tool was used to assess bias in randomized controlled trials (RCTs), and the ROBINS-I tool was applied for non-randomized studies. Meta-analyses were performed using R 4.2.0 and RevMan 5.3 software.ResultsA total of 16 studies (2 RCTs and 14 retrospective cohort studies) involving 1,409 patients (822 in the ICA group and 587 in the DCA group) were included. No statistically significant differences were observed between the two groups in operative time (SMD = 0.10, 95% CI: -0.23 to 0.44, P = 0.55), intraoperative blood loss (SMD = 0.34, 95% CI: -0.19 to 0.86, P = 0.21), or length of hospital stay (SMD = -0.37, 95% CI: -1.14 to 0.40, P = 0.34). However, the ICA group had significantly higher risks of total complications (OR = 2.74, 95% CI: 1.89–3.98, P < 0.00001), anastomosis-related complications (OR = 3.46, 95% CI: 2.32–5.15, P < 0.00001), and postoperative anastomotic leakage (OR = 2.79, 95% CI: 1.71–4.57, P < 0.0001) compared to the DCA group. There were no significant differences in local recurrence rate (OR = 1.02, 95% CI: 0.40–2.63, P = 0.98) or distant metastasis rate (OR = 1.51, 95% CI: 0.89–2.54, P = 0.13). Publication bias assessment revealed no substantial asymmetry in key outcomes, and sensitivity analyses confirmed the stability and robustness of the findings.ConclusionCompared with ICA, DCA is associated with significantly lower risks of overall complications, anastomotic complications, and anastomotic leakage in sphincter-preserving surgery for LRC, without compromising oncological safety. It demonstrates comparable performance in core perioperative indicators and may offer particular advantages for patients seeking minimally invasive approaches, those unable to tolerate stomas, or those at high risk of anastomotic failure. Therefore, DCA represents a viable and potentially preferable surgical option in the management of LRC. This study strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement and was registered on the PROSPERO international systematic review registration platform (registration number: CRD420251233006).